The Location of Extrinsic Afferent and Efferent Neurons Innervating the Stomach and Colon in Rat - Tarakçi, Berrin; Vaillant, Camille (My University, 1999)
The location of extrinsic afferent and efferent neurons projecting to the rat gastrointestinal tract were mapped using the retrograde tracer, True Blue (TB). Injection of retrograde tracer, TB into stomach, proximal colon and distal colon resulted in labelled cells in the dorsal root ganglia. Cells were also labelled in the nodose ganglia following injection of tracer into stomach and proximal colon. TB-labelled cells were also seen in the prevertebral ganglia (coeliacomesenteric complex and inferior mesenteric ganglion), after injection of TB into the stomach, proximal and distal colon. Many TB-labelled cells were detected in the dorsal motor nucleus of the vagus (DMNX) following injection of tracer into stomach. Labelled cells were less numerous following injection of tracer into the distal colon.
Keywords: Afferent neuron; Colon; Efferent neuron; Rat; Retrograde tracer; Stomach